Prerequisites for Agricultural Sector Innovative Development in the Context of European Integration Processes (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article considers the necessity of an innovative development in the agricultural sector within a number of economic indicators. The priority and advantages of innovative development in the agricultural sector are proved. The role of the labor productivity in the agriculture innovative development is determined basing on comparison with the similar indicators of European countries. The dynamics of foreign trade in agrarian products over the past five years has been analyzed and the reasons affecting its change have been determined. The influence of the total crop area and crop yield indicators on the agricultural efficiency is determined. Therefore a system of prerequisites for the innovative development of the Urkainian agrarian sector is formed. It comprises the social, economic and technological components.
Keywords: agricultural sector, agriculture, innovations, European integration, innovative development of the agricultural sector.